In Patients With Obesity, the Number of Adipose Tissue Mast Cells Is Significantly Lower in Subjects With Type 2 Diabetes - Lopez-Perez, David; Redruello-Romero, Anaïs; Garcia-Rubio, Jesús; Arana, Carlos; Garcia-Escudero, Luis A.; Tamayo, Francisco; Puentes-Pardo, Jose D.; Moreno-SanJuan, Sara; Salmeron, Javier; Blanco, Armando; Galvez, Julio; Leon, Josefa; et al. (Frontiers in Immunology, 2021)
Type 2 diabetes (T2D) is a rising global health problem mainly caused by obesity and a sedentary lifestyle. In healthy individuals, white adipose tissue (WAT) has a relevant homeostatic role in glucose metabolism, energy storage, and endocrine signaling. Mast cells contribute to these functions promoting WAT angiogenesis and adipogenesis. In T2D patients, inflammation dramatically impacts WAT functioning, which results in the recruitment of several leukocytes, including monocytes, that enhance this inflammation. Accordingly, the macrophages population rises as the WAT inflammation increases during the T2D status worsening. Since mast cell progenitors cannot arrive at WAT, the amount of WAT mast cells depends on how the new microenvironment affects progenitor and differentiated mast cells. Here, we employed a flow cytometry-based approach to analyze the number of mast cells from omental white adipose tissue (o-WAT) and subcutaneous white adipose tissue (s-WAT) in a cohort of 100 obese patients. Additionally, we measured the number of mast cell progenitors in a subcohort of 15 patients. The cohort was divided into non-T2D, pre-T2D, and T2D patients. Importantly, T2D patients have a mild T2D condition (HbA1c <7%). The number of mast cells and mast cell progenitors decreases in both o-WAT and s-WAT as the T2D status worsens. In the case of mast cells in o-WAT, there were statistically significant differences between non-T2D and T2D groups (p=0.0031), together with pre-T2D and T2D groups (p=0.0097). However, in s-WAT, the differences are only between non-T2D and T2D groups (p=0.047). These differences have been obtained with patients with a mild T2D condition. Therefore, little changes in the glycemic control have a huge impact on the number of mast cells in WAT, especially in o-WAT. Due to the importance of mast cells in WAT physiology, their decrease can reduce the capacity of WAT, especially o-WAT, to store lipids and cause hypoxic cell deaths that will trigger inflammation. Therefore the drop of WAT mast cells can contribute to the deterioration of T2D patients.